Advancements in pH-Responsive nanoparticles for osteoarthritis treatment: Opportunities and challenges - Liao, Shuai; Jia, Shicheng; Yue, Yaohang; Zeng, Hui; Lin, Jianjin; Liu, Peng (Frontiers in Bioengineering and Biotechnology, 2024)
Osteoarthritis (OA) is a degenerative disease associated with age and obesity. With the increasing aging of the global population, more and more OA patients have brought a heavy economic burden to society. Drugs and surgery in traditional treatment regimens often fail to achieve the desired outcome. With the rapid development of nanomaterials delivery system, a large number of studies are committed to using nanomaterials as carriers to achieve efficient treatment of osteoarthritis through effective loading and delivery of bioactive ingredients (drugs, genes, enzymes, etc.) based on special pathological background such as weak acid microenvironment of synovial fluid in the joint cavity of osteoarthritis patients. This review summarizes the latest progress of pH-responsive nanoparticles in the treatment of osteoarthritis (OA), emphasizes the principle of targeted drug delivery using the acidic microenvironment in the inflammatory joint, and further discusses the composition, synthesis, response (release) mechanism, target selection, application and latest research results of nanoparticles. It also reveals the challenges and future directions of this promising field.Osteoarthritis (OA) is a degenerative disease linked to aging and obesity. The global aging population has led to an increasing number of OA patients, imposing a significant economic burden on society. Traditional drugs treatment methods often fail to achieve satisfactory outcomes. With the rapid advancement of nanomaterial delivery systems, numerous studies have focused on utilizing nanomaterials as carriers to achieve efficient OA treatment by effectively loading and delivering bioactive ingredients (e.g., drugs, nucleic acids) tailored to the unique pathological conditions, such as the weakly acidic microenvironment of synovial fluid in OA patients. This review highlights the latest advancements in the use of pH-responsive nanoparticles for OA treatment, emphasizing the principle of targeted drug delivery leveraging the acidic microenvironment of inflamed joints. It further discusses the composition, synthesis, response mechanism, target selection, application, and recent research findings of nanoparticles, while also addressing the challenges and future directions in this promising field.